2020
DOI: 10.3889/oamjms.2020.5138
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Plasma Hypoxia Inducible Factor 1α in Type 2 Diabetes Mellitus with Malignancy and Without Malignancy

Abstract: BACKGROUND: Diabetes mellitus was associated with hypoxia condition and result ischemia and induced neovascularization and other forms of the cell adaptation in response to the tissue concentrations of low oxygen levels. Hypoxia-Inducible Factor 1 alpha a marker of the cell adaptation as a hypoxic cell response which was due of chronic hiperglycemia. AIM: The aim of this study to know the relationship between Hba1c and plasma HIF-1 α level at type 2 diabetes mellitus patients. METHODS: The cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Rusdiana et al, (37) revealed that patients with T2DM who have increased HIF-1α levels have a worse prognosis than those who have lower concentrations because high HIF-1α increases the risk of cancer and diabetic complications. Higher blood HIF-1α concentrations may play a role in vascular calcification in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Rusdiana et al, (37) revealed that patients with T2DM who have increased HIF-1α levels have a worse prognosis than those who have lower concentrations because high HIF-1α increases the risk of cancer and diabetic complications. Higher blood HIF-1α concentrations may play a role in vascular calcification in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies might support the major role of HIF-1α level as an independent risk factor in vascular and valvular calcification, making it a potential therapeutic target for preventing cardiovascular events in CKD patients [ 1 , 65 , 66 ].…”
Section: Hifs and Vascular Calcificationsmentioning
confidence: 99%
“…Li G et al also showed that elevated serum HIF-1α may contribute to coronary artery calcification (CAC) by CT scanning data analysis of 405 asymptomatic patients with type 2 diabetes mellitus, showing 61.1% sensitivity and 87.6% specificity for predicting CAC extent in this special group of patients [ 66 ].…”
Section: Hifs and Vascular Calcificationsmentioning
confidence: 99%
“…H ypoxia-inducible factor-1 alpha (HIF-1α) is a transcription factor that plays a crucial role in angiogenesis [ 1 ] and cellular responses to hypoxia [ 2 ]. During hypoxic condition, HIF-1α is stabilized and enters the nucleus to bind to other cofactors and activates the hypoxia response element of certain gene promoters [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such pathway involves in the development of intimal hyperplasia (IH), a condition characterized by the thickening of the inner lining of blood vessels, which is a common complication in arteriovenous fistula (AVF) creation [ 3 ]. In the case of AVF creation, the local oxygen diffusion from the arterial lumen may be insufficient due to intimal thickening and inflammation, resulting in a hypoxic environment that leads to the overexpression of HIF-1α [ 1 ].…”
Section: Introductionmentioning
confidence: 99%